The Power of Digital Engagement: Unveiling How Social Media Shapes Customer Responsiveness in the Food and Beverage Industry - Nada Sarkis; Nada Jabbour Al Maalouf; Souha Al Geitany (Administrative Sciences, 2025)
Social media platforms have become essential tools for businesses aiming to engage audiences through innovative communication, particularly in the food and beverage industry. This study explores the impact of three core digital marketing strategies, namely, social media advertisements, electronic word of mouth, and digital influencers, on customer responsiveness in the Lebanese food and beverage sector. Based on a cross-sectional survey of 400 participants, the findings reveal that social media advertisements significantly and positively influence customer responsiveness (β = 0.227, p < 0.001). Likewise, electronic word of mouth strongly predicts customer responsiveness (β = 0.453, p < 0.001), affirming the power of customer-generated content in shaping brand perceptions. Furthermore, the presence of digital influencers emerged as a significant predictor of consumer reaction (β = 0.236, p < 0.001), suggesting that consumers regard influencers as credible sources when making food-related decisions. Among all predictors, electronic word of mouth demonstrated the strongest effect. Control variables such as gender, age, and social media usage intensity showed no significant effect on customer responsiveness. These findings underscore the strategic value of rich media content and peer influence in shaping consumer behavior in the food and beverage industry. The study offers practical insights for marketers seeking to enhance customer engagement and brand responsiveness in digital spaces.